Semiotic Analysis of Teacher’s Role Representation in Kungfu Panda 4 by DreamWorks Animation - Alfarizi, Farid (Yayasan Pendidikan Bima Berilmu, 2025)
This study aims to analyze the representation of the teacher’s role in the film Kung Fu Panda 4 using Charles Sanders Peirce’s semiotic approach. The research focuses on how visual signs, dialogues, and cultural symbols are constructed to represent the figure of the teacher as an educator, mentor, motivator, and moral role model. This study employs a descriptive qualitative method, with the primary data source being the Kung Fu Panda 4 film produced by DreamWorks Animation. Data were collected through documentation techniques by repeatedly watching the film, noting key scenes, and classifying the signs based on Peirce’s categories of icons, indexes, and symbols. The findings reveal that the teacher’s role is represented through icons in the form of Po’s gestures and visualizations as an educator, indexes through cause-and-effect relationships between the teacher’s instructions and the students’ responses, and symbols involving language, moral values, and cultural artifacts. The discussion emphasizes that popular media, particularly animated films, not only serve as entertainment but also act as a medium for delivering educational values. This study contributes to the understanding of teacher representation in popular media and highlights the potential of animated films as an alternative educational medium.